SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2020
DOI: 10.2118/196250-ms
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Potential of Handil Shallow Oil Reservoir by Using Resin Sand Consolidation Technique

Abstract: Handil Field is a mature oil and gas field located in Mahakam Delta, East Kalimantan, Indonesia, developed since 1975. Handil reservoirs were deposited in a fluvio-deltaic environment. Oil reservoirs mainly located in shallow zone, whereas gas bearing reservoirs are mainly located in lower main until deep zone. Handil shallow zone consists of multi layer reservoirs located at depth 200 to 1500 m TVDSS. This zone is penetrated by different kinds of completion well techniques: gravel pack well for shallow zone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Moreover, the production rate was increased twice the production rate with other sand control method, (namely thru tubing screen) [57]. Hadi et al [58] used an epoxy resin to consolidate a sand formation in Mahakam Delta, East Kalimantan, Indonesia. They showed that the compressive strength and the permeability were 614-1816 psi, and 100-1068 md, respectively [58].…”
Section: Epoxy Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the production rate was increased twice the production rate with other sand control method, (namely thru tubing screen) [57]. Hadi et al [58] used an epoxy resin to consolidate a sand formation in Mahakam Delta, East Kalimantan, Indonesia. They showed that the compressive strength and the permeability were 614-1816 psi, and 100-1068 md, respectively [58].…”
Section: Epoxy Resinmentioning
confidence: 99%
“…Hadi et al [58] used an epoxy resin to consolidate a sand formation in Mahakam Delta, East Kalimantan, Indonesia. They showed that the compressive strength and the permeability were 614-1816 psi, and 100-1068 md, respectively [58]. Palencia et al [14] applied an epoxy resin to control a sand formation.…”
Section: Epoxy Resinmentioning
confidence: 99%
“…Handil fi eld had a sand problem near some well bores with gravel pack completion and they had been treated by sand consolidation chemical to improve the formation strength and enhance a maximum sand free rate (Mahardhini, et al, 2015). Gravel pack is commonly used as completion technique and also using resin sand consolidation (SCON) to overcome sand problem in Handil Field (Hadi, et al, 2019). The strategy to remedy the sand problem were to tested several types of chemical sand consolidation and choose the best fi t and performance for matrix consolidation.…”
Section: Introductionmentioning
confidence: 99%